2019
DOI: 10.1186/s13063-018-3087-4
|View full text |Cite
|
Sign up to set email alerts
|

Vagus nerve stimulation for pediatric patients with intractable epilepsy between 3 and 6 years of age: study protocol for a double-blind, randomized control trial

Abstract: BackgroundRecent clinical observations have reported the potential benefit of vagus nerve stimulation (VNS) as an adjunctive therapy for pediatric epilepsy. Preliminary evidence suggests that VNS treatment is effective for seizure reduction and mental development in young participants between 3 and 6 years of age who suffer from intractable epilepsy. However, robust clinical evidence for quantifying the difference of the efficacy and safety of VNS treatment in this specific patient population has yet to be rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 69 publications
0
20
0
Order By: Relevance
“…Other studies have shown similar levels of efficacy in pediatric and adult patients in VNS [25]. The rate of response improves over time.…”
Section: Vagus Nerve Stimulationmentioning
confidence: 64%
“…Other studies have shown similar levels of efficacy in pediatric and adult patients in VNS [25]. The rate of response improves over time.…”
Section: Vagus Nerve Stimulationmentioning
confidence: 64%
“…The Chinese version of GDS was revised by the Chinese Pediatric Association in 1986 and has been shown to have strong internal reliability and validity 21. It has been widely used to evaluate the function of the nervous system22 and to identify whether the nerve muscle or sensory system is defective 23. It is also used to clinically diagnose developmental delay in infants and children 24.…”
Section: Methodsmentioning
confidence: 99%
“…Potential therapies to address seizures cases in childhood that end in refractory epilepsy envisage nervous vagus stimulation (VNS) to reduce the pro-inflammatory cytokines and neurofeedback protocols to modulate the seizures activity. Current guidelines in VNS, which is an invasive procedure, suggest its usefulness in pediatric patients with intractable epilepsy that are resistant to antiepileptic drugs [ 58 ]. VMS works on stimulation frequency on the left vagus nerve with a specific pulse generator device set to a 20–30 Hz pulse frequency with a pulse width of 250–500 µs [ 59 ].…”
Section: Figure A1mentioning
confidence: 99%